ENGAGING STUDENTS SPEAKING SKILL USING GOOGLE MEET PLATFORM: STUDENTS PERCEPTION - Nisa Halimatusyadiyah (Journal of English Education Program (JEEP), 2022)
This study was conducted to find out students perception of engaging speaking skill using Google Meet platform and to find out the students perceptions of speaking skill using Google Meet platform. This study used a qualitative case study, and the data were taken through online classroom observation and close-ended questionnaire. Twenty four speaking students in the first semester of the English education department in one private university in Ciamis were involved in this study.  In analyzing the data of observation, the researcher classified, interpreted and commented the results of observation from google meet application. The data from the students’ questionnaire item were analyzed by using percentage compilation. Based on the finding, there are three key points of the present research. First, Google Meet online was conducted in one private university in Ciamis to improve students’ engagement speaking skill. Second, the students were generally perceives google meet as an application that enables them to learn English optimally, with enjoyed, relax, and enthusiasm. Third, google meet application gave students more opportunity to practice English rather than regular classroom.